Affective control and life satisfaction in thalassemics - Carmela Mento (Universidad de San Buenaventura, 2015)
Background. Thalassemia is a chronic disease that can lead to an impact on psychological functioning and social behavior of patients. However, still little is known about the specific psychological aspects of the disease, such as the degree of tension, life satisfaction and affective control, especially in adult patients.Aim. The purpose of this study is to investigate whether patients with thalassemia have specific psychological pattern relating to the dimensions of tension, satisfaction and quality of life, management of affection.Method. We evaluated 31 patients with thalassemia major and intermedia (19 women and 12 men) aged between 18 and 50 years (M = 34 + 16), belonging to the Complex Unit of Medical Genetics. For the evaluation were used the Profile of Mood States (POMS), the Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q) and the Rorschach test.Results. The findings show an inverse relationship between the levels of self-reported tension and the affective control indicators at Rorschach. Life satisfaction, instead, seems to vary according to the severity of the disease - major vs. intermediate - and the type of therapy.Conclusions. An understanding of the psychological mechanisms involved in thalassemia, both self-reported and projective, can contribute to a wider patient take-over, by considering the subjective aspects related to the psychological and socio-emotional well-being, fundamental in the care compliance.